Leviticus 19:32 in Times of Elder Care Crisis in Nigeria: A Hermeneutical Analysis - Uroko, Favour Chukwuemeka (Besari: Journal of Social and Cultural Studies, 2025)
The research aims to establish a theological foundation for elder care that integrates biblical principles with traditional Nigerian values while responding to current challenges faced by Nigeria's ageing population. The problem addressed is the growing disconnect between Nigeria's expressed cultural values of elder reverence and the lived reality of many elderly Nigerians who experience various forms of abuse, neglect, and marginalisation. Methodologically, this research employs a multidisciplinary approach integrating (1) exegetical analysis of Leviticus 19:32 within its historical and theological context; (2) review of gerontological literature on elder experiences and challenges in Nigeria; (3) comparative analysis of biblical principles and traditional Nigerian cultural values regarding elder care; and (4) application of contextualised hermeneutics to bridge ancient text and contemporary social challenges. The findings reveal that Leviticus 19:32 establishes elder care as a theological imperative rather than merely a cultural preference, connecting respect for the aged directly with reverence for God. This divine mandate encompasses both symbolic gestures (rising in their presence) and practical support structures that recognise the intrinsic dignity of elderly persons. The research identifies substantial alignment between biblical principles and traditional Nigerian values regarding elder reverence while highlighting how both systems are challenged by contemporary socioeconomic realities. The study further demonstrates how religious institutions can play a crucial role in revitalising elder care practices through their extensive community networks and moral influence.